Volcanism and the Greenland ice cores: A new tephrochronological framework for the last glacial-interglacial transition (LGIT) based on cryptotephra deposits in three ice cores. (15th September 2022) - Cook, Eliza; Abbott, Peter M.; Pearce, Nick J.G.; Mojtabavi, Seyedhamidreza; Svensson, Anders; Bourne, Anna J.; Rasmussen, Sune O.; Seierstad, Inger K.; Vinther, Bo M.; Harrison, Joseph; Street, Elliott; Steffensen, Jørgen Peder; et al.
Abstract: Chemical profiles from Greenland ice cores show that the frequency of volcanism was higher during the last glacial-interglacial transition (LGIT) and early Holocene, (17–9 ka b2k) than in any other period during the last 110 kyr. This increased frequency has partly been linked to climate-driven melting of the Icelandic ice sheet during the last deglaciation, with regional isostatic changes thought to alter mantle viscosity and lead to more eruptions. Our study is the first to construct a comprehensive tephrochronological framework from Greenland ice cores over the LGIT to aid in the reconstruction of volcanic activity over this period. The framework is based on extensive high-resolution sampling of three Greenland ice cores between 17.4 and 11.6 ka b2k and comprises a total of 64 cryptotephra deposits from the NGRIP, GRIP and NEEM ice cores. We show that many of these tephras are preserved within the core without an associated chemical signature in the ice, which implies that reconstructions of volcanism based solely on glacio-chemical indicators might underestimate the number of events. Single glass shards from each deposit were geochemically characterised to trace the volcanic source and many of these deposits could be correlated between cores. We show that the 64 deposits represent tephra deposits from 42 separate volcanic events, and of these, 39 are from Iceland, two from the north Pacific region (Japan and USA) and one has an unknown source. Six deposits can be correlated to terrestrial and/or marine tephra deposits in the Northern Hemisphere and the remaining 36 are unreported in other archives. We did not locate tephra from the compositionally distinctive Laacher See eruption (∼13 ka b2k) in our records. Combining our new discoveries with the previously published tephra framework, raises the number of individual tephra horizons found in Greenland ice over this interval to 50. This significantly improves the regional tephrochronological framework, our knowledge of the eruptive history of Iceland during the LGIT and provides new tephra constraints over key LGIT climate events. Consequentially, this framework can guide sampling strategies of future tephra studies in the terrestrial and marine realms aiming to link these records to the Greenland ice cores to assess regional climate synchroneity. Highlights: This study improves our knowledge of Icelandic volcanism during the LGIT. 64 cryptotephras found in Greenland ice, from 42 separate volcanic events. A previously unreported basaltic deposit constrains Holocene onset. 2 deposits from the north Pacific: Mt. St. Helens J-Set and Towada To-H (Japan).